2010
DOI: 10.1177/1545109710373828
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Study: Does Lower Extremity Night Splinting Assist in the Management of Painful Peripheral Neuropathy in the HIV/AIDS Population?

Abstract: Introduction: The pain associated with peripheral neuropathy (PN) observed in patients living with HIV/AIDS represents a difficult complication to manage. Participants: A total of 22 participants with a diagnosis of PN were recruited to assess the effects of using night splints on pain and sleep quality. Methods: For 3 weeks, the participants were instructed to use bilateral night splints and given an exercise regimen for 3 additional weeks. Scores from pain and sleep questionnaires were analyzed using repeate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…Further, clinical expression of neuropathic pain results in impairment of inhibitory modulation systems, anxiety and depression (Colloca et al 2017 ; Keltner et al 2012 ; Malvar et al 2015 ) which have been associated with sleep problems (Colloca et al 2017 ; Sandoval, Runft & Roddey 2010 ) and opioid use disorders (Malvar et al 2015 ). According to Malvar et al ( 2015 ) factors such as opioid use disorder, older age, being female, current and past ART treatment as well as a lack of HIV suppression predict neuropathic pain (Malvar et al 2015 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, clinical expression of neuropathic pain results in impairment of inhibitory modulation systems, anxiety and depression (Colloca et al 2017 ; Keltner et al 2012 ; Malvar et al 2015 ) which have been associated with sleep problems (Colloca et al 2017 ; Sandoval, Runft & Roddey 2010 ) and opioid use disorders (Malvar et al 2015 ). According to Malvar et al ( 2015 ) factors such as opioid use disorder, older age, being female, current and past ART treatment as well as a lack of HIV suppression predict neuropathic pain (Malvar et al 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…The severe symptoms, such as ageing and other comorbidities amongst persons using ART, increase the risk of disability which impacts on multiple aspects of daily living (Biraguma & Rhoda 2012 ; Cade et al 2004 ; Mehta et al 2010 ). Management of symptoms or impairments (such as neuropathic pain), using splints (Sandoval et al 2010 ) and physiotherapist-supervised exercise, has shown promising outcomes (Taylor et al 2007 ; Tumusiime et al 2019 ). This has the potential to influence the deployment of physiotherapists and other rehabilitation professions in universal health care and practice where exercise becomes a key strategy to prevent disability and activity limitation.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of the current study are congruent with those reported in a pilot study on the use of LE splints to manage pain in PLWHA and DSPN. 12 The authors reported a 20% reduction in pain and sleep scores following a 3-week nighttime use of LE splints. A moderate effect size was attributed to the splints for pain and sleep scores during that LE splints trial.…”
Section: Discussionmentioning
confidence: 98%
“…7 In addition to pain, sleep disturbances have been reported in people living with end-stage renal disease-related neuropathies and HIV-related DSPN. 11,12 A review of systemic diseases' impact on sleep suggests that alterations in sleep stages and increases in sleep disturbances are associated with HIV disease progression into AIDS. 13 The impact of DSPN-related pain on self-perceived sleep quality remains uncertain based on the limited number of reports in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…In the HAART era, research pertaining to physical therapy and HIV/AIDS is sparse and narrow in scope, investigating efficacy [13][14][15][16][17][18][19][20][21][22] or knowledge. 11,23,24 Studies examining efficacy of physical therapy intervention in patients with HIV infection are mainly limited to specific techniques in small patient subpopulations [13][14][15][16] or case reports. [17][18][19] In addition, Hilburn et al 20 developed and evaluated a gross motor screening test for infants with HIV infection in developing countries.…”
mentioning
confidence: 99%